Pengaruh Metode Inquiry Terhadap Kemampuan Koneksi Matematika Kelas X SMK Swasta Teruna Padangsidimpuan - andika saputra harahap; Yuni Rhamayanti; Puspa Riani Nasution (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2025)
This study aims to determine the effect of the inquiry method on students' mathematical connection ability in Class X of SMK Swasta Teruna Padangsidimpuan. Mathematical connection ability is an essential competency in mathematics learning that includes students’ ability to connect mathematical concepts, relate mathematics to real-life situations, and apply various mathematical representations. This research is a quasi-experimental study using a Non-Equivalent Control Group Design. The sample consisted of two classes: the experimental class, which received treatment using the inquiry method, and the control class, which was taught using conventional methods, with 20 students in each class. The instrument used in this study was a mathematical connection ability test in the form of essay questions that had been validated.The results showed that the average post-test score in the experimental class was 77.05, while in the control class it was 53.90. The independent sample t-test resulted in a significance value of 0.000 < 0.05, indicating a significant difference between the two groups. Therefore, it can be concluded that the inquiry learning method significantly affects the improvement of students’ mathematical connection ability.